Effect of various post-extrusion tempering on performance of AA2024 tubes fabricated by shear assisted processing and extrusion. (May 2022) - Reza-E-Rabby, Md.; Wang, Tianhao; Canfield, Nathan; Roosendaal, Timothy; Taysom, Brandon Scott; Graff, Daniel; Herling, Darrell; Whalen, Scott
Highlights: Extrusion speed of ShAPE for AA2024-T371 billets reaches 7.4 m/min. The yield strength of the AA2024-T8510 ShAPE-extruded tube is 32% higher than typical ASM and minimum ASTM values. The elongation at break of ShAPE-extruded AA2024-T8510 tubes is doubled than typical ASM and minimum ASTM values. Graphical Abstract: ga1 Abstract: Aluminum alloy 2024 tubes were extruded using the shear assisted processing and extrusion (ShAPE) method. Extrusions were produced at 7.4 m/min at 482 °C using the ShAPE technique which is more than doubles the previous highest extrusion speed for AA2024 using conventional extrusion methods. Standard T3510 and T8510 post extrusion heat treatments were applied to improve the mechanical performance of ShAPE extruded AA2024 tube. The ultimate tensile and yield strength of the AA2024-T8510 ShAPE-extruded tube are 522.0 ± 3.3 MPa and 510.7 ± 3.3 MPa, which are respectively 18% and 32% higher than typical ASM International and minimum American Society for Testing and Materials (ASTM) values. The elongation at break of ShAPE-extruded AA2024-T8510 tubes is two times higher than the typical ASM International and minimum ASTM values. This improved ductility is attributed to the refinement of grain size and secondary phases as well as the uniform dispersion of sub-micron strengthening precipitates formed during the ShAPE processing.